1989
DOI: 10.1002/cyto.990100211
|View full text |Cite
|
Sign up to set email alerts
|

Detection of mRNA in flow‐sorted cells

Abstract: Cells were sorted onto nitrocellulose filters which were saturated with a lysing cocktail designed to preferentially immobilize cellular mRNA. After washing, these filters were incubated with 32P-labeled specific DNA probes. We used the phorbol esterAipopolysaccharide (PMA + LPS) co-induction of IL-1 mRNA and CD13 expression in U937 cells to demonstrate the specificity of the technique. In addition we used the abundant expression of cfos in U937 to demonstrate linearity. IL-1 beta mRNA is readily discernable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The sort blot technique was performed with modifications of the method previously described (Dunne et al, 1989). Changes in the method included modifications in the sort blot module design and the use of nylon membranes instead of nitrocellulose.…”
Section: Sort Blotmentioning
confidence: 99%
“…The sort blot technique was performed with modifications of the method previously described (Dunne et al, 1989). Changes in the method included modifications in the sort blot module design and the use of nylon membranes instead of nitrocellulose.…”
Section: Sort Blotmentioning
confidence: 99%
“…Several reports have shown that intact RNA can be recovered from cells flow-sorted after labeling of cytoplasmic epithelial cell-specific cytokeratins (2,4,7,8). Whole-cell sorting typically involves treating cells in organic fixatives, followed by staining with tissuespecific antibodies in an aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…They flow-sorted living cells directly onto nitrocellulose filters which were saturated with a lysing cocktail designed to preferentially immobilize cellular mRNA. After hybridization of these filters with 32p-labeled specific DNA probes, they were able to study the phorbol ester/lipopolysaccharide induction of IL-1 mRNA in U937 cells, and they demonstrated the linearity of the method by exploiting the abundant expression of the c-los in these cells [15]. IL-I mRNA was readily detectable autoradiographically from as few as 5 000 induced cells, and liquid scintillation counting demonstrated a good linearity in c-fos quantification over the range of 1 000 to 60 000 cells sorted per filter.…”
Section: Specific Mrna Quantificationmentioning
confidence: 99%